Development of a Critical Thinking Skills Assessment Instrument on Dynamic Electricity for High School Students - Suratni Agustinih; Wasino; Agus Yuwono (Physics Communication, 2025)
The development of critical thinking skills is a curriculum mandate in Indonesia to prepare students for global challenges, yet existing assessments often fail to effectively measure these higher-order competencies. This study aims to analyze the developmental needs, characteristics, feasibility of an assessment instrument, and the effectiveness of its use in evaluating the critical thinking skills (CTS) of high school students on the topic of dynamic electricity. This is a research and development (R&D) study that employs the Four-D Model (define, design, develop, disseminate), as developed by Thiagarajan. The sample consisted of 30 students for a small-scale trial and 150 students for a large-scale trial. Data were collected through interviews, tests, questionnaires, and documentation. The data obtained from these methods were then analyzed using the Rasch Model to evaluate the psychometric properties of the instrument. The instrument was characterized by high-cognitive-level multiple-choice questions administered via the Google Forms platform integrated with AutoProctor. The research findings revealed the need to develop a critical thinking skills assessment instrument that meets the requirements of teachers, students, and conceptual frameworks.  The instrument's validity was established through two methods. First, an expert validation process yielded an average Aiken's V coefficient of 0.93. Second, data from empirical trials analyzed with the Rasch Model showed that all items met the ZSTD fit criteria for validity (-2.0 < ZSTD < +2.0). Item reliability was 0.74 and 0.92, with Cronbach's Alpha values of 0.84 and 0.87 (reliable). The item difficulty level was evenly distributed, the item discrimination index was 3.44 (good), and the instrument was free from bias. The average score across the 6 CTS indicators was 79.82, indicating that the assessment instrument for critical thinking skills on dynamic electricity is both feasible and effective for use.